Effect of Contact Angle and Mass Fraction on Droplet Freezing Process - Liu Shengchun; Zhang Xue; Dai Baomin; Jiang Tingting (Zhileng xuebao)
The solidification/melting model of FLUENT software was used to numerically study the influence of contact angle and mass fraction on the freezing process of pure water and sodium chloride solution on the cold surface. Meanwhile, copper was chosen as the hydrophilic surface and nanometer film as the hydrophobic surface, and the freezing process of droplets under different surface characteristics was experimentally studied. The results show that the freezing characteristics of the droplet on the surface of the plate are related to the surface contact angle and mass fraction. When the solution mass fraction is fixed, a smaller contact angle results in a faster droplet freezing rate and a shorter complete freezing time. At the beginning of the freezing process, the smaller the contact angle, the lower the bottom temperature of the droplet. When the freezing time and the droplet height were the same, the temperature and liquid fraction on the surface of the droplet were lower than those inside the droplet. At the same contact angle, the solution mass fraction is inversely proportional to the initial freezing temperature of the droplet and directly proportional to the complete freezing time. The comparison between the experimental results and the simulation results shows that the freezing time of different mass fractions of sodium chloride droplets exhibits the same trend when the contact angle is 60° and 100°, but the experimental value is greater than the simulated value.